2005
DOI: 10.1093/nar/gki343
|View full text |Cite
|
Sign up to set email alerts
|

Mutational comparison of the single-domained APOBEC3C and double-domained APOBEC3F/G anti-retroviral cytidine deaminases provides insight into their DNA target site specificities

Abstract: Human APOBEC3F and APOBEC3G are double-domained deaminases that can catalyze dC→dU deamination in HIV-1 and MLV retroviral DNA replication intermediates, targeting T–C or C–C dinucleotides, respectively. HIV-1 antagonizes their action through its vif gene product, which has been shown (at least in the case of APOBEC3G) to interact with the N-terminal domain of the deaminase, triggering its degradation. Here, we compare APOBEC3F and APOBEC3G to APOBEC3C, a single-domained deaminase that can also act on both HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
173
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(187 citation statements)
references
References 66 publications
(81 reference statements)
13
173
1
Order By: Relevance
“…Transfection experiments then revealed that APOBEC3G was packaged into HIV-1 particles and acted to deaminate cytosine to uracil in the first-strand DNA of the HIV replication intermediates (13,18,22,23,49). Similar antilentiviral activities have subsequently been noted for APOBEC3F and APOBEC3C (3,17,20,45,48,51). That APOBEC3F and APOBEC3G can indeed act on HIV-1 during infection of humans is indicated by analysis of the sequences of hypermutated HIV-1 genomes isolated from infected individuals (2, 3, 4, 12, 20, 44).…”
mentioning
confidence: 64%
“…Transfection experiments then revealed that APOBEC3G was packaged into HIV-1 particles and acted to deaminate cytosine to uracil in the first-strand DNA of the HIV replication intermediates (13,18,22,23,49). Similar antilentiviral activities have subsequently been noted for APOBEC3F and APOBEC3C (3,17,20,45,48,51). That APOBEC3F and APOBEC3G can indeed act on HIV-1 during infection of humans is indicated by analysis of the sequences of hypermutated HIV-1 genomes isolated from infected individuals (2, 3, 4, 12, 20, 44).…”
mentioning
confidence: 64%
“…Flag-tagged A2, A3F and A3G expression plasmids were constructed previously (Langlois et al, 2005). The single-cycle HIV[p8.9] pseudovirus expressing EGFP and the replicative Moloney murine leukaemia virus (M-MLV) expressing EGFP as an Env-EGFP fusion have been previously described (Bélanger et al, 2013;Langlois et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The single-cycle HIV[p8.9] pseudovirus expressing EGFP and the replicative Moloney murine leukaemia virus (M-MLV) expressing EGFP as an Env-EGFP fusion have been previously described (Bélanger et al, 2013;Langlois et al, 2009). HIV[p8.9] (referred to as HIV-1 DVif pseudovirus in the text) expresses EGFP from an internal spleen focus-forming virus promoter (Langlois et al, 2005). M-MLV expresses EGFP from the viral LTR promoter as a nested fusion protein with Env where it is inserted in the proline-rich region of the protein (Sliva et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient transfections were performed using Lipofectamine LTX (Invitrogen -Catalog #15338100) and GeneJuice (Novagen -Catalog #70967-3) according to manufacturer's instructions. Lentiviral infections of Caco-2 cells were performed as detailed in Langlois et al 72 All transfections with multiple plasmids were performed using an equal amount of overall plasmid DNA. Differences in the amount of DNA from experimental constructs were filled with an empty construct.…”
Section: Plasmidsmentioning
confidence: 99%